Cost-Benefit Rules in General Equilibrium - Boadway, Robin W. (Review of Economic Studies, 1975)
Journal Article Cost-benefit Rules in General Equilibrium Get access Robin W. Boadway Robin W. Boadway Queen's University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 3, July 1975, Pages 361–374, https://doi.org/10.2307/2296850 Published: 01 July 1975